Aversive Affect Versus Racism as Predictors of Racial Discrimination in Helping. Issue 4 (4th July 2019) - McManus, Jessica L.; Saucier, Donald A.; O'Dea, Conor J.; Bernard, Donte L.
Abstract: We examined aversive affect and racism as predictors of differences in helping White versus Black targets. According to aversive racism theory, Whites may express egalitarian attitudes but experience discomfort in interracial interactions, producing discrimination. Participants completed racism measures and reported their likelihood of helping White or Black targets. Racism negligibly predicted discriminatory helping across studies. In Studies 2 and 3, participants experiencing aversive affect were less likely to help Black than White targets. Results demonstrate negative feelings, more so than racial biases, impacts discriminatory helping. We hope to inspire future research examining why White bystanders experience aversion in interracial helping.